The Development of Computer Supported Conceptual Change Text on Buoyant Force - Dwi Yulia Handayani; Andi Suhandi; Endang Ahmad Djuanda (Jurnal Multidisiplin Madani, 2022)
The development of computer supported Conceptual Change Text (CCText) is based on a number of misconceptions of buoyant force encountered by students. Computer supported CCT is a technique which is used to correct students’ prior knowledge and prepare students for the new and scientific knowledge. Computer supported CCText is started with extracting the initial idea regarding the concept that students had, continued by cognitive conflict stage which functions to challenge the misconception that students had, and then followed by the scientific explanation of the mistakes which have been formulated previously and therefore the students were given the questions to confirm the changed concept that students had at last. This research involved fourty participants. The participants consist of senior high school students which divided into two classes; experimental class and control class. The experimental class used computer supported CCText and conceptual change learning model to overcome misconceptions they encountered, whereas the control class only used conceptual change learning model. The result of this research indicates that the experimental class which used computer supported CCText is more significant to reduce alternative conceptions that students had than the control class.